Relationship between soil chemical characteristics and soil-borne fungi in tomato tunnels of Punjab, Pakistan - Javaid, Arshad; Anjum, Freeha; Mahmood, Rashid; Akhtar, Naureen (Bangladesh Journal of Botany, 2019)
Soil pH, ECe, N, K, P and organic matter in 12 soil samples collected from different tomato (Solanum lycopersicum L.) tunnels were in the range of 7.7 - 8.3, 0.40 - 2.45 dS/cm, 0.02 - 0.10%, 40 - 282 ppm, 12 - 123 ppm and 0.42 - 2.02%, respectively. A total of 20 fungal species belonging to ten genera, namely Aspergilus, Alternaria, Cladosporium, Drechslera, Emericella, Fusarium, Mortierella, Mucor, Penicillium and Sclerotium were isolated from the soil samples using direct and dilution plate techniques. Total number of fungal colonies ranged from 450 - 2700/g soil in different soil samples. Among these, number of colonies of saprophytic and pathogenic fungi were 432 - 2070 and 10 - 954/g soil sample, respectively. Number of pathogenic colonies was significantly and positively correlated with soil organic matter and N. The soil organic matter and nitrogen favoured population of pathogenic fungi in tomato tunnels.